The Phenomenon of Campalagian Market Community Conformity Regarding Traffic Light Rules - Andi Alfian Ashari; Muh. Nur Hidayat Nurdin; Tri Sulastri (ARRUS Journal of Social Sciences and Humanities, 2023)
The community in Campalagian market exhibits negligent behavior in their daily activities, where there is a traffic light in front of the market but the community seems to ignore its presence. It starts with a few individuals who are not compliant, followed by others, resulting in traffic light signals being disregarded. This study aims to understand the phenomenon of conformity behavior within the community and the factors that contribute to this conformity behavior. The research methodology employed in this study is qualitative with a phenomenological approach. Data collection techniques used in this research involve observations and interviews conducted with respondents who meet the criteria. The research respondents consist of three individuals, namely S, SU, and MH. The results of the research indicate that individual conformity behavior can be observed by examining behavior that follows the actions of other individuals and their understanding of traffic light rules. Factors that shape conformity behavior include the community's indifference toward traffic lights, many drivers violating traffic lights, pressure from other drivers, ingrained thought patterns within the community, and community habits. The findings of this research can serve as a source of information for optimizing facilities and formulating policies aimed at increasing awareness within the Campalagian market community regarding traffic rules.